1995
DOI: 10.1080/09542299.1995.11083251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selenite and selenate on plant uptake of cadmium by kidney bean(Phaseolus mungo)with reference to Cd—Se interaction

Abstract: Pot culture experiments have been conducted to study the effect of selenite and selenate pretreatment on the uptake and translocation of root-absorbed cadmium in the kidney bean plant, irrigated with 2 1-Lg mL -1 of Cd. A statistically significant reduction in cadmium uptake with increasing concentration of selenite and selenate (0.5-6.0 1-Lg mL -1 ) has been observed. Selenite treatment is found to be more effective in decreasing cadmium uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Selenite was more easily reduced than selenate (Doran 1982). This would be consistent with observations presented in the literature showing that selenite was more effective to reduce Cd concentration in plants than selenate (Shanker et al 1995(Shanker et al , 1996Zhou et al 2017;Yu et al 2018). However, we were unable to confirm these observations, which would have required a wider range of selenate concentrations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Selenite was more easily reduced than selenate (Doran 1982). This would be consistent with observations presented in the literature showing that selenite was more effective to reduce Cd concentration in plants than selenate (Shanker et al 1995(Shanker et al , 1996Zhou et al 2017;Yu et al 2018). However, we were unable to confirm these observations, which would have required a wider range of selenate concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…One reaction proposed is the formation of nonbioavailable cadmium selenide (CdSe) in soil first mentioned by Shanker et al (1995). However, so far, no evidence for the formation of this compound in soil has been published.…”
Section: Discussionmentioning
confidence: 99%
“…Kabata-Pendias and Pendias (2001) 34 reported that an increased content of Se inhibited the absorption of some heavy metals including Cd. Shanker et al 38 reported a reduction in Cd uptake in kidney bean plants (Phaseolus mungo L.) grown in pot experiments, caused by an increased concentration of selenite and selenate solutions applied to the soil (0.5-6.0 g mL −1 ). Several references reported that low dosages of Se could protect plants by reducing their J Sci Food Agric 2018; 98: 4971-4977 © 2018 Society of Chemical Industry wileyonlinelibrary.com/jsfa uptake of toxic elements, such as As and Pb.…”
Section: Effects Of Se On the Uptake Of Other Elementsmentioning
confidence: 99%
“…Studies of the Se-Cd interaction in plants have not been as conclusive as studies in animals. In pot experiments, addition of Se reduced Cd accumulation in kidney bean and maize (Shanker et al 1995;Shanker et al 1996). The authors suggested that the acidic environment of the rhizosphere allowed the reduction of selenite and, to a lesser extent, selenate to occur so that unavailable Cd-Se complexes could form (Shanker et al 1995;Shanker et al 1996).…”
mentioning
confidence: 99%
“…In pot experiments, addition of Se reduced Cd accumulation in kidney bean and maize (Shanker et al 1995;Shanker et al 1996). The authors suggested that the acidic environment of the rhizosphere allowed the reduction of selenite and, to a lesser extent, selenate to occur so that unavailable Cd-Se complexes could form (Shanker et al 1995;Shanker et al 1996). In another study with two soil types, Se reduced the concentration of Cd in lettuce, but had little effect on Cd in the aerial portion of wheat (Cary 1981).…”
mentioning
confidence: 99%